2008
DOI: 10.1097/mop.0b013e32830c6ef1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic abdominal pain in children: what to do following the medical evaluation

Abstract: As more is learned about different therapies for recurrent abdominal pain, an integrative approach that blends these interventions may become increasingly common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(20 reference statements)
0
5
0
3
Order By: Relevance
“…Suele asociarse con manifestaciones psicosomáticas. 11,12 Por su parte, la prevalencia del DME guarda una relación directa con la edad. Las causas más frecuentes en la adolescencia son traumatismos, el síndrome por sobrecarga y la lumbalgia.…”
Section: Artículo Originalunclassified
“…Suele asociarse con manifestaciones psicosomáticas. 11,12 Por su parte, la prevalencia del DME guarda una relación directa con la edad. Las causas más frecuentes en la adolescencia son traumatismos, el síndrome por sobrecarga y la lumbalgia.…”
Section: Artículo Originalunclassified
“…kullanıldığını belirtmişlerdir. Banez [32] çalışmasında ebeveynlerin karnı ağrıyan çocuklarına nane bitkisinin yağını kullandıklarını bildirmiştir. Day ve ark.…”
Section: Gereç Ve Yöntemunclassified
“…Also, the severity of the disorder can be affected to the child's clinical outcome 24) . The causes of RAP are complex and do not provide a single concept of causations.…”
Section: Etiologymentioning
confidence: 99%
“…Recent study showed three different therapeutic approaches such as voluntary procedures 86,87) , dietary fiber 88∼90) , and behavioral-cognitive managements 82,91∼94) . According the guidelines of recent research 24) , cognitive and behavioral therapies arise as a …”
Section: Managementmentioning
confidence: 99%